R&D and Regional Regeneration. The Case of Alba Subregion in Romania - Zizi Goschin; Georgiana-Gloria Goschin (European Regional Science Association (ERSA), 2014)
Innovation and competitiveness are important factors for promoting economic growth not only nationally, but regionally as well. In Romania, research, development and innovation could be among the factors that are accountable for the increasing regional disparities, as the territorial distribution of R&D resources is very unbalanced. Romania is currently trying to define a regional strategy for R&D, as well as appropriate policies and priorities for innovation at regional level. In this context we address the issue of the regional intensity of R&D as one of the main determinants of economic growth in Alba county (subregion NUTS 3) in Romania. The Alba subregion can be considered an obvious example of a successful economic transformation since its GDP per capita increased more than 2 times in 10 years, based on a high rate of economic growth. We have analysed the regional intensity of R&D, measured as the share of total research and development expenditures in regional GDP, and have developed an economic growth model that aimed to capture the influence of R&D intensity alongside labour productivity, employment rate, human capital, the share of manufacturing in total economic activity, the extent of private entrepreneurship, and a dummy variable for economic crisis. The results point to a highly significant impact of research and development intensity on the long-run economic development of Alba county, as measured by GDP per capita. This positive effect of R&D on the economic performance in Alba county can be largely attributed to the creation and modernization of the business support infrastructure aimed at developing industrial parks, business incubators, industrial and scientific clusters, technological and logistic platforms, centers for research and transfer of technology, etc. These structures are designed to support business development in areas affected by industrial restructuring, but also economic activities in other areas with development potential in the county, providing favorable conditions for productive SME development, which can further contribute to economic development and job creation in both the underdeveloped and the rising areas in this subregion.
Keywords: R11; R58; 330; economic growth; regional regeneration; Alba county; Romania